Future Directions of Municipal Solid Waste Management in Africa - Simelane, Thokozani; Mohee, Romeela (Book collections on Project MUSE., 2015)
Transformation and rapid population growth in Africa indicates that urbanisation is one of the key determinants of the future of social dynamics and development of the continent. Linked to these changes are increased production levels of Municipal Solid Waste. This book provides recommendations and solutions that derive from current situations, experiences and observations in Africa. This book is a 'must read' for urban planners, environmental engineering students and lecturers, environmental consultants and policy-makers. The book can also be of great help to municipal authorities, as it outlines future directions of Municipal Solid Waste management. These need to be considered by the municipal authorities of most African countries.